2019
DOI: 10.1177/1528083719866934
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite and short-cut fiber-based wet-laid filter media for particles and heavy metal ion removal of wastewater

Abstract: As development of industrialization grows constantly, the purification of hazardous solid particles and ions is one of the most important topics in environment and ecosystem. In this report, we designed and developed a novel and advanced type of filter media for the removal of both solid particles and hazardous ions, we choose Cs+ and Ca2+ here, by enclosing zeolite in wet-laid nonwoven media. The performance of the prepared filter media was evaluated by continuous sorption experiments, which were followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…First, a small amount of inclusions are added to the matrix material to homogenize the whole material. Then add the inclusion material, homogenize it, repeat the project continuously, and finally obtain the mechanical properties of the composite with a certain volume content of inclusions [ 10 ]. The cyclic steps of adding and homogenizing by the differential method are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…First, a small amount of inclusions are added to the matrix material to homogenize the whole material. Then add the inclusion material, homogenize it, repeat the project continuously, and finally obtain the mechanical properties of the composite with a certain volume content of inclusions [ 10 ]. The cyclic steps of adding and homogenizing by the differential method are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The parameters settings of GA are selected that how to provide a search space with suitable diversity to avoid early convergence. In order to evaluate the cost function, a single objective optimization problem based on the Euclidean distance between the target and individual has been defined as equation (12).…”
Section: Optimization Problemmentioning
confidence: 99%
“…Despite studies with regard to the process of coating zeolite on the surface and composites of the flexible material, there are still some difficulties in the fabrication of flexible zeolite, such a complex process for degradation and development of properties. [10][11][12][13] The electrospinning technique, which is an easy-toimplement, economical, and simple method, can be used for increasing efficiency in this respect and flexible zeolite fibers are created using biocompatible polymers. 10,[14][15][16] In order to fabricate a bio-scaffold, bioengineers should carefully select biocompatible polymers with relative degradability for remodeling the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al investigated the current situation of heavy metal element pollution in rural soil of the Pearl River Delta and showed that in addition to the pollution sources such as chemical fertilizer, pesticides, and livestock and poultry, industrial and other pollution also had a great impact. In addition, the industrial soil in the research area is dominated by excessive Cu, while the planting soil is dominated by excessive Cd [6]. Mukeba et al investigated the spatial distribution and source analysis of 12 heavy metals on the surface of Lianyuan, a typical coal mining city, and the results showed that most heavy metals were related to human activities.…”
Section: Literature Reviewmentioning
confidence: 99%